Association between Periodontitis and Hyperglycemia - Marília Terezinha Gonçalves OLIVEIRA; Paulo Guilherme Santos FURTADO; Rafaella Ferreira Cordeiro e CARDOSO; Ana Carolina Dupim SOUZA; Rafael Paschoal Esteves LIMA; Santuza Maria Souza de MENDONÇA (Faculdade São Leopoldo Mandic, 2018)
Objective: The objective of this study was to analyze the prevalence of undiagnosed hyperglycemia in individuals with periodontitis. Methods: The sample was composed of randomly selected individuals that had signed-up for treatment at the Newton Paiva University dental clinic. The volunteers were divided in two groups, the first composed by individuals without periodontitis (n = 30) and the second by individuals with periodontitis (n = 20). All participants answered a questionnaire about habits and overall health condition. Salivary flow was quantified and periodontal examination evaluated bleeding when probed, probing depth and clinical attachment level. Through laboratory tests, the fasting glucose and the glycated hemoglobin levels were quantified. Results: In the sample studied a higher percentage of individuals with hyperglycemia among those with periodontitis than those without periodontitis was identified. Conclusion: It is suggested, therefore, that the request of laboratory tests to check glucose levels becomes a part of the dental treatment protocol of individuals with periodontitis.